Mechanotransduction regulates inflammation responses of epicardial adipocytes in cardiovascular diseases - Liu, Xiaoliang; Liu, Lei; Zhao, Junfei; Wang, Hua; Li, Yifei (Frontiers in Endocrinology, 2022)
Adipose tissue is a crucial regulator in maintaining cardiovascular homeostasis by secreting various bioactive products to mediate the physiological function of the cardiovascular system. Accumulating evidence shows that adipose tissue disorders contribute to several kinds of cardiovascular disease (CVD). Furthermore, the adipose tissue would present various biological effects depending on its tissue localization and metabolic statuses, deciding the individual cardiometabolic risk. Crosstalk between adipose and myocardial tissue is involved in the pathophysiological process of arrhythmogenic right ventricular cardiomyopathy (ARVC), cardiac fibrosis, heart failure, and myocardial infarction/atherosclerosis. The abnormal distribution of adipose tissue in the heart might yield direct and/or indirect effects on cardiac function. Moreover, mechanical transduction is critical for adipocytes in differentiation, proliferation, functional maturity, and homeostasis maintenance. Therefore, understanding the features of mechanotransduction pathways in the cellular ontogeny of adipose tissue is vital for underlining the development of adipocytes involved in cardiovascular disorders, which would preliminarily contribute positive implications on a novel therapeutic invention for cardiovascular diseases. In this review, we aim to clarify the role of mechanical stress in cardiac adipocyte homeostasis and its interplay with maintaining cardiac function.